Estrategias de marketing en el Comercial Moreira de la Parroquia San Juan. - Montero Icaza, Meliza Lizbeth (2022)
Marketing strategies are crucial and important, apply then within the Company correctly and appropriately, since they are the ones that guarantee their timely growth. Establishing priorities in terms of clients id precisely this factor that will allow the Company to keep in constant development, since there ir no relational marketing that is directly with the consumer. For this reason, the present case study is to know how and what are the marketing satrategies that have beem applied throughout this entire trajectory as a Company, an esencial context to achieve juicy sucess in the Company. The investigation analize the inforamation through current clients as well as ambiguous clients, in addition, an interview was applied ti the Manager-Owner to obtain the corresponding data. Finally, it is conclued that Commercial Moreira does not follow a method duly endorsed by professionals that allow it ti introduce know lwdge in said place, an aspect that denotes the an aspect that denotes the scarcity of sales strategias, resulting in weaknesses eith repect to the competition. The scenario described is imposible for the Company to créate a competitive advantage.